Optical coherence tomography angiography in comparison with other multimodal imaging techniques in punctate inner choroidopathy. Issue 1 (26th March 2018) - Pohlmann, Dominika; Pleyer, Uwe; Joussen, Antonia M; Winterhalter, Sibylle
Abstract : Aims: To characterise punctate lesions and choroidal neovascularisation (CNV) in eyes with punctate inner choroidopathy (PIC) using current standard multimodal imaging techniques and optical coherence tomography angiography (OCTA). Methods: In our prospective, single-centre study, 20 individuals with PIC underwent imaging with spectral-domain optical coherence tomography (SD-OCT), fluorescein angiography (FA), indocyanine green angiography, fundus autofluorescence, fundus colour photography and OCTA. Results: Thirty-two eyes of 20 patients were affected. Eight (20%) eyes revealed typical punctate lesions, while 24 (60%) eyes had confirmed CNV on SD-OCT and FA in addition to punctate lesions. Of these 24 eyes with CNV, a reoccurrence of active CNV was detected in 5 (21%) eyes, a residual fluid in 3 (13%) eyes, while 16 (67%) eyes were defined as being stable. On OCTA, CNV was classified as having 'lacy wheel', 'pruned large-trunk' and 'dead tree aspect' vessel shapes with or without areas of non-perfusion. The disease activity was dependent on several predictors in the regression analysis such as intraretinal fluid (p=0.0014), CNV type (p=0.0199), leakage (p<0.0001) and hypoperfusion/non-perfusion (p<0.0001) on OCTA. Conclusion: OCTA offers additional valuable insight into the current standard multimodal imaging techniques used for characterisation of PIC. This imaging technique can be a useful tool for analysis of disease activity.